To solve the equation, we need to isolate x.
First, let's simplify the left side of the equation:
4(3 - x)^(4/3) - 5 = 59
Next, we can simplify the exponent by multiplying the exponent outside the parenthesis with the exponent inside the parenthesis:
4(3 - x)^(4/3) - 5 = 59
4(3 - x)^(4/3) = 64
Now, we can remove the parentheses by raising both sides of the equation to the power of 3/4:
[4(3 - x)^(4/3)]^(3/4) = 64^(3/4)
(3 - x) = 64^(3/4)
To solve for x, we can subtract 3 from both sides of the equation:
3 - x = 64^(3/4) - 3
Finally, we can solve for x by subtracting the right side of the equation from 3:
x = 3 - (64^(3/4) - 3)
x = 6 - 64^(3/4)
What is the solution of the equation?
4 left parenthesis 3 minus x right parenthesis Superscript StartFraction 4 over 3 EndFraction baseline minus 5 equals 59
1 answer